If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+5=-5-2x
We move all terms to the left:
3x+5-(-5-2x)=0
We add all the numbers together, and all the variables
3x-(-2x-5)+5=0
We get rid of parentheses
3x+2x+5+5=0
We add all the numbers together, and all the variables
5x+10=0
We move all terms containing x to the left, all other terms to the right
5x=-10
x=-10/5
x=-2
| 0.6x-0.7(-0.2x-0.8)=9.3 | | 2r/3=10/3 | | 36=6+18x+28x+2 | | 40p/4=54 | | 4×(5+1)=i | | 12n=11 | | (8x+16)(3x+51)=100 | | 19=-4(b-8) | | 14-3x=-30 | | 8+3b=(-13) | | 7x-(3x+14)=10 | | 120/r=30 | | 7p+13=-36 | | (x+1)^2=16 | | 2a=5/7 | | 3(h+11)+-12=-9 | | 2x×x=36 | | 21+3b=36 | | 9000-300(t+t)=t | | 7/3x-4=6/2x+4 | | 0.3x+1.8=0.4(x+5)0.2 | | (2y2+-2y=1)/(y-2) | | 6x-(x+5)=10 | | .35m=9.8 | | 64=4(x-8) | | 45+20x-65=180 | | 6(x+2)-9x=-3(x-4) | | 1/4x-22=3/4x+22 | | 8x+-6=-38 | | 36w=36 | | 5x+4-7x=5-2x+13 | | 13=2(h+7)-5 |